FOOD SECURITY AND COMPARATIVE ANALYSIS OF SITUATION IN SERBIA AND NEIGHBOURING COUNTRIES - Božić, Dragica; Nikolić, Marija (Economics of Agriculture, 2020)
The concept of food security has expanded significantly over time, and due to its importance, it is on the list of priorities of the UN Sustainable Development Goals. The aim of this paper is to analyze the state of individual dimensions and key indicators of food security in Serbia and selected neighboring countries using the Global Food Security Index (GFSI). The index was created in 2012 by the Economist Intelligence Unit and it is calculated every year to measure the risk of food insecurity in individual countries. The latest data indicate that Serbia has the worst rank among the neighboring countries. The analysis showed that two GFSI indicators for Serbia (gross domestic product per capita and public expenditure on agriculture) are the worst evaluated and represent the main limitations of improving food security in Serbia.